2016
DOI: 10.7554/elife.15552
|View full text |Cite
|
Sign up to set email alerts
|

Recreating the synthesis of starch granules in yeast

Abstract: Starch, as the major nutritional component of our staple crops and a feedstock for industry, is a vital plant product. It is composed of glucose polymers that form massive semi-crystalline granules. Its precise structure and composition determine its functionality and thus applications; however, there is no versatile model system allowing the relationships between the biosynthetic apparatus, glucan structure and properties to be explored. Here, we expressed the core Arabidopsis starch-biosynthesis pathway in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(75 citation statements)
references
References 119 publications
10
65
0
Order By: Relevance
“…In yeast cells, starch-like synthesis was recreated by introduction of Arabidopsis SSs without plant enzymes related to synthesis of a primer, thus the intrinsic primers of yeast seems to be sufficient for the formation of starch like polyglucans. Furthermore, the experiments again showed that SS4 can be substituted by other SSs, as starch-like polyglucans were observed not exclusively when SS4 was introduced ( Pfister et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast cells, starch-like synthesis was recreated by introduction of Arabidopsis SSs without plant enzymes related to synthesis of a primer, thus the intrinsic primers of yeast seems to be sufficient for the formation of starch like polyglucans. Furthermore, the experiments again showed that SS4 can be substituted by other SSs, as starch-like polyglucans were observed not exclusively when SS4 was introduced ( Pfister et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Starch also has favorable thermoplastic properties and is biodegradable ( Thakur and Thakur, 2016 , Imre and Pukánszky, 2015 , Jiménez et al, 2012 , Zhang et al, 2014 ). Starch is mainly made up of two kinds of glucose macromolecules, amylose and amylopectin ( Pérez and Bertoft, 2010 ), however functional and structural dissimilarities are present between different types ( Carpenter et al, 2017 ), thus the efficiency of starch as a raw material for bioplastics depends upon its specific structure and composition ( Pfister et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The SS1, SS2, and SS3 isoforms are involved primarily in amylopectin synthesis, and Arabidopsis mutants lacking any of these isoforms have altered amylopectin structure (Delvallé et al, 2005;Zhang et al, 2005Zhang et al, , 2008. These SS isoforms act together with branching enzymes and debranching enzymes (ISOAMYLASE), which are required for the formation and correct arrangement of the branch points (Delatte et al, 2005;Dumez et al, 2006;Streb et al, 2008;Pfister et al, 2014Pfister et al, , 2016. The GRANULE-BOUND STARCH SYNTHASE (GBSS) elongates amylose chains and is tightly associated with the starch granule (Smith et al, 2004;Seung et al, 2015).…”
Section: Introductionmentioning
confidence: 99%